Parent perspectives of the challenging aspects of disclosing a child's epilepsy diagnosis to others: Why don't they tell?. (March 2017) - Benson, Ailbhe; Lambert, Veronica; Gallagher, Pamela; Shahwan, Amre; Austin, Joan K
Objectives: This study aimed to explore the challenges parents of children with epilepsy (CWE) experienced when deciding to disclose their child's epilepsy diagnosis to others. Methods: Using a qualitative exploratory design, interviews were conducted with 34 parents (27 mothers and 7 fathers) of 29 CWE (aged 6–16 years). Parents were recruited from a neurology clinic of a specialist children's hospital and from a national epilepsy association. Interviews were directed by a semi-structured guide informed by a review of the literature. Data were transcribed verbatim, imported into NVivo, coded and thematically analysed. Results: Findings revealed five themes representative of the core disclosure challenges parents encountered, many of which promoted concealment and/or selective disclosure, namely: seeking normalcy for the child, the invisibility of epilepsy, negative reactions to disclosure, contending with poor public perceptions of epilepsy and coming to terms with the diagnosis. Discussion: This study presents crucial information for healthcare professionals (HCPs) who help families to navigate the disclosure decision-making process. Providing HCPs working with families living with epilepsy with insight into diagnosis disclosure challenges will enable them to recognise the support needs of parents and work collaboratively with families to tackle such difficulties, ultimately improving their psychosocial wellbeing.